Evolution of Metallicity in Vanadium Dioxide by Creation of Oxygen Vacancies - Zhang, Zhen; Zuo, Fan; Wan, Chenghao; Dutta, Aveek; Kim, Jongbum; Rensberg, Jura; Nawrodt, Ronny; Park, Helen Hejin; Larrabee, Thomas J.; Guan, Xiaofei; Zhou, You; Prokes, S. M.; et al. (Physical Review Applied, 2017)
Tuning of the electronic state of correlated materials is key to their eventual use in advanced electronics and photonics. The prototypical correlated oxide (VO2) is insulating at room temperature and transforms to a metallic state when heated to 67 °C (340 K). We report the emergence of a metallic state that is preserved down to 1.8 K by annealing thin films of VO2 at an ultralow oxygen partial pressure (PO2∼10-24 atm). The films can be reverted back to their original state by annealing in oxygen, and this process can be iterated multiple times. The metallic phase created by oxygen deficiency has a tetragonal rutile structure and contains a large number of oxygen vacancies far beyond the solubility at equilibrium (greater than approximately 50 times). The oxygen starvation reduces the oxidation state of vanadium from V4+ to V3+ and leads to the metallization. The extent of resistance reduction (concurrent with tuning of optical properties) can be controlled by the time-temperature envelope of the annealing conditions since the process is diffusionally driven. This experimental platform, which can extensively tune oxygen vacancies in correlated oxides, provides an approach to study emergent phases and defect-mediated adaptive electronic and structural phase boundary crossovers.
CRIS-Team Scopus Importer:2023-04-20